2014
DOI: 10.14202/vetworld.2014.765-769
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and polymerase chain reaction-based identification of Riemerella anatipestifer from ducks in Kerala, India

Abstract: The aim was to isolate and characterize Riemerella anatipestifer organisms from disease outbreaks in ducks in Kerala.Materials and Methods: Ducklings, suspected of Riemerella infection, were sacrificed and subjected to post-mortem examination. Heart blood smears and impression smears from liver and spleen were examined for the presence of pathogenic organisms. Heart blood, lung, liver, and spleen collected aseptically from the birds were subjected to isolation trials in brain heart infusion agar and 10% bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…A species-specific PCR assay developed by Kardos et al, (2007), revealed the presence of 546 bp PCR product. Similar results were observed by Soman et al, (2014) andShancy, (2015) to confirm the RA isolates. This PCR assay, could easily replace the traditional method of identification to identify the isolate from clinical samples, as it was highly sensitive and specific.…”
Section: Resultssupporting
confidence: 89%
“…A species-specific PCR assay developed by Kardos et al, (2007), revealed the presence of 546 bp PCR product. Similar results were observed by Soman et al, (2014) andShancy, (2015) to confirm the RA isolates. This PCR assay, could easily replace the traditional method of identification to identify the isolate from clinical samples, as it was highly sensitive and specific.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, R. anatipestifer isolates were highly sensitive to amikacin, imipenem and rifampin. These results nearly agreed with Zhong et al (2009) ; Chang et al (2019) ; and Soman et al (2014) . The multiple drug resistances were found in all R. anatipestifer isolates (Table 2) .…”
supporting
confidence: 76%
“…For more accurate diagnosis conventionally biochemical tests including Indole production, Methyl-red test (MR), Voges-Proskauer (VP) test, H 2 S production, and Oxidase and Catalase test, sugar fermentation (glucose, lactose, maltose, mannitol, dextrose, sucrose) test have been used and produced the similar results mentioned in (Sarker et al 2017); fermentation of dextrose, lactose, maltose, mannitol, glucose, sucrose, MR test positive, VP and Indole negative, and Catalase positive. Similarly, oxidase test positive and H 2 S negative mentioned by (Surya et al 2016; Shancy et al2018).The PCR is considered as gold standard, regarding speci city, sensitivity, and reliability for detecting microbial causal agents of diseases(Soman et al 2014). In this study, PCR was performed targeting the Riemerella species speci c gene designed by(Kardos et al 2007) and gyrB gene primarily.…”
mentioning
confidence: 92%